Selection of DNA Cleavage Sites by Topoisomerase II Results from Enzyme-Induced Flexibility of DNA. Issue 4 (18th April 2019) - Jang, Yunsu; Son, Heyjin; Lee, Sang-Wook; Hwang, Wonseok; Jung, Seung-Ryoung; Byl, Jo Ann W.; Osheroff, Neil; Lee, Sanghwa
Summary: Topoisomerase II cleaves DNA at preferred sequences with different efficiencies; however, the mechanism of cleavage site selection is not known. Here we used single-molecule fluorescence assays that monitor several critical steps of DNA-topoisomerase II interactions, including binding/dissociation, bending/straightening, and cleavage/religation, and reveal that the cleavage site is selected mainly during the bending step. Furthermore, despite the sensitivity of the bending rate to the DNA sequence, it is not an intrinsic property of the DNA itself. Rather, it is determined by protein-DNA interactions. Graphical Abstract: Highlights: Reaction rates for individual steps in the DNA cleavage reaction are characterized Kinetic pathway of divalent ions in the DNA cleavage reaction is revealed Sequence-preferential DNA bending is induced for the cleavage site selection It is determined by protein-DNA interactions rather than by the intrinsic property Abstract : Jang et al. describe single-molecule fluorescence experiments that monitor the individual steps of topoisomerase II. Kinetic analysis for six different sequences reveal that the cleavage site is selected in the DNA bending step. It is determined by protein-DNA interactions rather than by an intrinsic property of the sequences.